Respuesta :

Answer:

[tex] a = \dfrac{5}{18} [/tex]

[tex]b = -\dfrac{1}{18}[/tex]

Step-by-step explanation:

You need to rationalize the fraction.

[tex] \dfrac{1}{5 + \sqrt{7}} = a + b\sqrt{7} [/tex]

[tex] \dfrac{1}{5 + \sqrt{7}} \times \dfrac{5 - \sqrt{7}}{5 - \sqrt{7}} = a + b\sqrt{7} [/tex]

[tex] \dfrac{5 - \sqrt{7}}{25 - 7} = a + b\sqrt{7} [/tex]

[tex] \dfrac{5 - \sqrt{7}}{18} = a + b\sqrt{7} [/tex]

[tex] \dfrac{5}{18} - \dfrac{1}{18}\sqrt{7} = a + b\sqrt{7} [/tex]

[tex] a = \dfrac{5}{18} [/tex]

[tex]b = -\dfrac{1}{18}[/tex]

ACCESS MORE